The chosen [videorecording (DVD)] - Kagan, Jeremy Paul; Schell, Maximilian; Steiger, Rod, 1925-2002; Benson, Robby; Miller, Barry, 1958-; Potok, Chaim (Distributed by Hen's Tooth Video, 2010)
The story of two teenage boys who become best friends despite huge differences in their upbringing. Danny is the son of an orthodox Hasidic Rabbi. Reuven comes from a progressive Jewish family whose father stands at the forefront of the battle for Israeli statehood. Danny's every moment is devoted to religious study, while Reuven plays jazz piano and is intensely interested in the changing world around him. Their family differences soon force both to make difficult choices.